Guidance on date marking and related food information: part 2 (food information). (22nd April 2021) - ,; Koutsoumanis, Konstantinos; Allende, Ana; Alvarez‐Ordóñez, Avelino; Bolton, Declan; Bover‐Cid, Sara; Chemaly, Marianne; Davies, Robert; De Cesare, Alessandra; Herman, Lieve; Hilbert, Friederike; Nauta, Maarten; et al.
Abstract: A risk‐based approach was used to develop guidance to be followed by food business operators (FBOs) when deciding on food information relating to storage conditions and/or time limits for consumption after opening a food package and thawing of frozen foods. After opening the package, contamination may occur, introducing new pathogens into the food and the intrinsic (e.g. pH and aw ), extrinsic (e.g. temperature and gas atmosphere) and implicit (e.g. interactions with competing background microbiota) factors may change, affecting microbiological food safety. Setting a time limit for consumption after opening the package (secondary shelf‐life) is complex in view of the many influencing factors and information gaps. A decision tree (DT) was developed to assist FBOs in deciding whether the time limit for consumption after opening, due to safety reasons, is potentially shorter than the initial 'best before' or 'use by' date of the product in its unopened package. For products where opening the package leads to a change of the type of pathogenic microorganisms present in the food and/or factors increasing their growth compared to the unopened product, a shorter time limit for consumption after opening would be appropriate. Freezing prevents the growth of pathogens, however, most pathogenic microorganisms may survive frozen storage, recover during thawing and then grow and/or produce toxins in the food, if conditions are favourable. Moreover, additional contamination may occur from hands, contact surfaces or contamination from other foods and utensils. Good practices for thawing should, from a food safety point of view, minimise growth of and contamination by pathogens between the food being thawed and other foods and/or contact surfaces, especially when removing the food from the package during thawing. Best practices for thawing foods are presented to support FBOs.